2018
DOI: 10.1096/fj.201800334
|View full text |Cite
|
Sign up to set email alerts
|

Cilia protein IFT88 regulates extracellular protease activity by optimizing LRP‐1–mediated endocytosis

Abstract: Matrix protease activity is fundamental to developmental tissue patterning and remains influential in adult homeostasis. In cartilage, the principal matrix proteoglycan is aggrecan, the protease-mediated catabolism of which defines arthritis; however, the pathophysiologic mechanisms that drive aberrant aggrecanolytic activity remain unclear. Human ciliopathies exhibit altered matrix, which has been proposed to be the result of dysregulated hedgehog signaling that is tuned within the primary cilium. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 61 publications
0
15
1
Order By: Relevance
“…We previously linked IFT88 to aggrecanase activity in vitro [16], but here found no correlations in gene expression to link observed atrophy to altered expression of proteases or LRP-1 (receptor for protease clearance). There were also no apparent increases in aggrecanase-mediated aggrecan neoepitope in situ.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…We previously linked IFT88 to aggrecanase activity in vitro [16], but here found no correlations in gene expression to link observed atrophy to altered expression of proteases or LRP-1 (receptor for protease clearance). There were also no apparent increases in aggrecanase-mediated aggrecan neoepitope in situ.…”
Section: Discussioncontrasting
confidence: 69%
“…The primary cilium has also been coined a 'mechanosensor', bending in response to fluid flow within the kidney, initiating downstream signaling pathways [14]. In vitro experiments in chondrocytes have implicated ciliary IFT88 both with compressioninduced production of extracellular matrix proteins [15] and impaired clearance of aggrecanases, resulting in exacerbated degradation of aggrecan [16].…”
Section: Introductionmentioning
confidence: 99%
“…Research in our own lab showed that LRP-1-mediated endocytosis of proteases is impaired in chondrocytes derived from the ORPK mutant mice. Co-culture of these cells with the purified matrix component aggrecan, and subsequent detection of protease-generated aggrecan neoepitopes, showed that ORPK chondrocytes have constitutively increased protease activity in vitro [108]. This increased activity was not associated with increased Hh signaling or increased mRNA levels of aggrecan-degrading proteases.…”
Section: Primary Cilia Have Been Associated With Endocytic Control Ofmentioning
confidence: 95%
“…Furthermore, the ciliary functional intraflagellar transport protein IFT20 is essential in regulating Hedgehog signalling transduction and affecting Golgi size to maintain a cartilaginous matrix and maintain the homeostasis of condylar cartilage (Figure ) . Disruption of ciliary trafficking protein IFT88 can also affect the extracellular protease activity and regulate the extracellular matrix remodelling of articular chondrocyte via regulating LRP‐1‐mediated endocytosis …”
Section: Primary Cilia and Cartilage Developmentmentioning
confidence: 99%